Categorías de hipertensión arterial y calidad de vida de los pacientes hipertensos diagnosticados del Gobierno Provincial de Loja - Jimbo Hoyos, Jhuliana Monserrath (2022)
Arterial hypertension is a highly prevalent disease in our environment and constitutes a serious public health problem, so quality of life is an important factor to evaluate the effectiveness of treatments and interventions in the health area. The purpose of this study was to classify the categories of arterial hypertension, identify the levels of quality of life and establish the relationship between both variables, in hypertensive patients diagnosed by the Provincial Government of Loja, during the period March 2020 - March 2021. The study had a quantitative, observational, cross-sectional approach; the sample consisted of 60 patients diagnosed with high blood pressure, who had their blood pressure (PA) measured and applied the High Blood Pressure Quality of Life Questionnaire (CHAL). Obtaining as results: 75% consisted of male patients and 25% female; the age groups comprised of young, mature and older adults, predominantly mature adults with 86.7%. 60% presented stage 2 hypertension; 25% stage 1 hypertension; 13.3% elevated BP and 1.7% normal BP. The levels of quality of life were recorded as very good in 61.7%, good in 35%, regular in 3.3%, and poor quality of life was not determined. The majority of patients in the four blood pressure categories recorded a very good quality of life, and the minority with stage 2 hypertension had a fair quality of life. Demonstrating that there is no relationship between the variables studied.